Pengaruh Penambahan Sari Kurma Terhadap Kualitas dan Aktivitas Antimikroba pada Dadih - Diva Mawaddah; Ulfayani Mayasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the additional concentration of date palm juice which can influence the quality of curd in terms of total LAB, pH value, antimicrobial activity and organoleptic characteristics including color, texture, aroma and taste. This research design used a Completely Randomized Design using 100ml of buffalo milk added with date juice, consisting of 4 treatments, namely P0 (without adding date juice), P1 (10%), P2 (15%), and P3 (20%). Research data was analyzed using ANOVA and Tukey's advanced test if there were differences in influence. The research results showed that Treatment P1 (10%) produced curd with the best characteristics in terms of total BAL 8.60×1011 CFU/ml, pH value 4.45, irradical inhibition zone formed with a diameter of 9.35 mm against Sterptococcus mutans. Meanwhile, in the organoleptic test, treatment P3 (20%) was the best curd chosen by the panelists including aroma 4.60 (liked very much), color 4.16 (liked very much), taste 4.40 (liked very much). However, in terms of texture, the panelists liked the curd treatment P0 (without adding date juice) 4.00 (liked). In conclusion, curd with the addition of date juice had a significantly different effect on total BAL, pH value, antimicrobial activity on Streptococcus mutans, aroma, texture and taste. However, there was no significant difference in color and antimicrobial activity for Candida albicans. Keywords: BAL, Curd, Dates